HEGEMONI AGAMA DI INDONESIA: PERSPEKTIF PASTORAL LINTAS AGAMA - Rynaldi Mahardika Situmeang (Diegesis : Jurnal Teologi, 2024)
This article aims to examine the religious hegemony that is currently occurring in Indonesia, where in several cases that have occurred over the last five years, the dominance of one religion over another religion is clear and occurs continuously. This can certainly damage the perfection of diversity in Indonesia itself, considering that diversity is one of the characteristics inherent in Indonesia's identity as a great nation. Religious hegemony in Indonesia is considered the "right" thing to do because of the power obtained from the dominance of the majority religion. Therefore, the author wants to conduct an cross-religious pastoral study in looking at issues of power faced by religion as a tool to make power appear legitimate. This study concludes with an ethical attitude based on the understanding that power is created, defeated and can be redeemed, which will help us to see what ethical attitude the church must take towards hegemony of power. The specific calling of the church is to understand and engage with both the structure and spirituality of oppressive institutions.